Korean Soap Operas, Telenovelas and Sci-fi Conspiracies: A Game-making Experience with Latin American Youth in London - Paula, Bruno de (Digital Culture and Education, 2021)
This paper explores a game-making programme for 14 Latin American migrants aged 13-18 in London/UK, carried out between October/2017-January/2018, where I investigated the relationships between game conventions, platforms and personal preferences in the curation of fluid identities through game production. Participants presented varying levels of affinity with games linked both to access issues and to other specific elements (e.g. perception of games in contemporary culture, gender). Questionnaires, observations, unstructured/semistructured interviews and gaming archives were employed to explore this participatory initiative and data was analysed through Multimodal Sociosemiotics. Findings remarked how shared understandings about digital games can find their way into platforms and act as “cultural-technical gatekeepers”, supporting or hindering the engagement with game-making of those often perceived as outsiders to gaming culture. This gatekeeping happens when there are “creative dissonances” between, for example, personal preferences and platforms aligned to normative/mainstream genres. These dissonances, however, can end up fostering subversive designs, contravening gaming conventions and potentially challenging traditional gaming boundaries. This insight is relevant for understanding “cultural-technical constraints” and subversive/non-mainstream game-making, especially in relation to innovation and appropriation of game-making resources/strategies by non-mainstream groups.
Number: 2
Keywords: 1-Jeux vidéo; 1-TV; 2-Recherche-création; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice PANDC; 5-Identités diasporiques; _Nettoyé

“Emergent Countries Play, Too!”: The Zeebo Console as a (Partial) Decolonial Project - Paula, Bruno de (Revista Contracampo, 2021)
The present paper discusses questions related to the histories of videogames, more specifically in how we approach videogames in Global South. By using Zeebo, a Brazilian console produced in the late 2000s as an epistemic tool, I discuss the limitations of universalist, mainstream-centric epistemological models for exploring videogames as cultural phenomena. By investigating Zeebo’s discourses about piracy and players in the Global South, I argue that this platform can be seen as a partial decolonial project, destabilising conventional historical narratives about South-North relationships in videogames, but refraining from challenging a mainstream, Global North oriented epistemology. This exploratory work, therefore, elaborates on how a decolonial project of history of videogames, one that is more epistemically just to Global South, could be sought.
Number: 2
Keywords: 1-Jeux vidéo; 2-Humanités numériques; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 4-Europe (lieu de production du savoir); 5-Créatrice; _Nettoyé

Introduction: American Game Studies - Jagoda, Patrick; Malkowski, Jennifer (American Literature, 2022)
In 2017, the American game designer Momo Pixel released the single-player, browser-based game Hair Nah. In this game, you play as Aeva, a Black woman taking trips to locations that include Osaka, Havana, and the Santa Monica Pier. As you move through levels on your journey—taking a taxi ride, traversing airport security, sitting on an airplane—you must slap away increasingly aggressive white hands that reach into the frame to touch your hair. Though Hair Nah taps into the genre of a casual button-mashing game, this interactive experience also explores the topic of microaggressions via unwanted hair touching. If you slap away enough hands on your travels, you reach a screen welcoming you to your destination with the message “YOU WIN!” but the caveat, “The game is over, but this experience isn’t. This is an issue that black women face daily. So a note to those who do it STOP THAT SHIT.”
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice LGBTQ+; _Nettoyé

Reconsidering Lost Opportunities for Diverse Representation - Nguyen, Josef (American Literature, 2022)
This article considers the cultural politics of frustrated potential for diverse representation in games by examining developer comments on the 1995 digital game I Have No Mouth, and I Must Scream, adapted from Harlan Ellison’s 1967 science fiction story of the same name. While Ellison’s story featured a gay man named Benny among the protagonists, the game developers adapted Benny without his original sexual identity. In a 2012 Game Informer magazine article, however, the developers reflected on their version of Benny as a “lost opportunity” for exploring gay identity. Rooted in discussion of this frustrated potential for a gay in-game Benny, this article interrogates a logic of lost opportunity for diverse representation present in game-development discourse, which manifests in a longing for more diverse characters that could have been but never came to be. This logic suggests particular ways that developers might conceive of diverse representation as simply a design issue under neoliberal logics of economic opportunity, commercial risk, and fetishized innovation—without meaningful consideration of political significance. Opposing this instrumentalization of frustrated diverse representation, this article draws on queer game studies and speculative design and literature to explore the possible contours and implications of diverse characters that never were more seriously than such comments typically do. Doing so demands more than romanticized longings for lost opportunities for diverse representation that treat this longing as the end in itself.
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Critical Distance - Critical Distance (Critical Distance)
Back in 2009, Critical Distance was founded to answer the question: “Where is all the good writing about games?” Our goal for the last 10 years has always been to facilitate dialogue. Through roundups, roundtables, podcasts, and critical compilations, we provide one place where all the most important discourse is collected together. We aim to build a foundation for ongoing conversations between developers, critics, educators and enthusiasts about critical issues in games culture. We are a compendium of the most incisive, thought-provoking, and remarkable discussion in and around games, keeping it archived for years to come. Our work has helped new writers to find their voice, educators to find resources to help their students develop critical thinking, and developers to become more reflective in their design practice.
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 2-Étude des représentations; 5-Auteur.rice PANDC; _Nettoyé

The Players' Realm: Studies on the Culture of Video Games and Gaming - Williams, James Patrick; Smith, Jonas Heide (McFarland, 2007)
"This study sketches some of the various trajectories of digital games in modern Western societies, looking at the growth and persistence of the moral panic that continues to accompany massive public interest in digital games. The book continues with a new phase of games research exemplified by systematic examination of specific aspects of digital games and gaming"–Provided by publisher.
OCLC: 700517982
Keywords: 1-Jeux vidéo; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 2-Étude des représentations; 5-Autrice; _Nettoyé

Hyperculturality, Globalization and Cultural Representation in Japanese Survival Horror - Ramírez-Moreno, Carlos (Replaying Japan, 2019)
This article presents the ways in which Japanese survival horror employs video games as a tool for cultural representation. First, it analyses the main differences between American and Japanese horror, and how the historical relationships of competition/collaboration between both have led to a constant exchange of cultural references present in their games. This relationship of domination/submission traces back to the post-war period in which the United States began exercising control over Japan. It is as a result of this period that Japanese terror begins to take shape and take its first steps towards the current J-Horror. Second, it analyses the work of game designer Keiichiro Toyama, namely Silent Hill and Siren, as a well-known example of the construction of a cultural identity halfway between the devotion to the Other and the respect for tradition. Finally, the article addresses other examples of Japanese survival horror to analyse more deeply which stance Japanese industry takes in this era of cultural globalization, or hyperculturality, which is seriously transforming our conception of culture in digital media.
Keywords: 1-Jeux vidéo; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Europe (lieu de production du savoir); _Nettoyé

Amateur Gold Farming in China: “Chinese Ingenuity,” Independence, and Critique - Liboriussen, Bjarke (Games and Culture, 2016)
Informed by a mix of theoretical sources and interviews with middle-class Chinese amateur gold farmers, this article argues that within China, the figure of the Chinese gold farmer might function as focus for reflection on Chineseness and China’s role in an increasingly interconnected world, rather than as a carrier of third-world stereotype as it tends to do in the West. The concept of shanzhai—often associated with sometimes comical, sometimes innovative Chinese copying of foreign consumer goods—is employed as a key analytical tool and helps highlight the themes of “Chinese ingenuity,” independence (from game operators and to some extent also parents), and critique (of games).
Keywords: 1-Jeux vidéo; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); _Nettoyé

Sinological-orientalism in Western News Media: Caricatures of Games Culture and Business - Wirman, Hanna (Games and Culture, 2016)
From gold farmers and ‘100 million brain-damaged online gamers’ to the world’s biggest game company and more players than US citizens, China seems like the cabinet of curiosities for the whole world of digital gaming. This article focuses on news coverage around Chinese gaming and presents three phases of such journalism. China’s emerging games market was most prominently featured between 1999 and 2005, while 2006-2011 focused on extreme play behavior in China. Most recently, a discourse of vast business opportunities and stabilizing markets has been presented by Western news media. In total more than 853 news articles are explored in parallel to the theoretical concept of Sinological-orientalism. This article suggests significant historical changes in the ways in which knowledge of Chinese gaming has been produced in English language news media.
Keywords: 1-Jeux vidéo; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Autrice; _Nettoyé

Japanese Console Games Popularization in China: Governance, Copycats, and Gamers - Liao, Sara X. T. (Games and Culture, 2016)
This article attempts to explore the popularization of Japanese console games in China in the past two decades, which reveals the tripartite relationship of the nation-state, transnational cultural power, and local agents.1 This study focuses on the formation and development of the console game industry in a non-Western context, where the society has undergone dramatic transformations and has been largely influenced by the globalization process. Encountering social anti-gaming discourse and cultural protectionism, the importation and distribution of Japanese console games did not get support from the state. However, it found its way to the audience and gained popularity through piracy, the black market, and the local agents’ appropriation, becoming an integrated part of many Chinese early gamers’ lives. This article draws upon the intersection of cultural globalization with game studies, calling for an investigation into the complexity of the game industry through its sociohistorical, political, and cultural environment.
Keywords: 1-Jeux vidéo; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

A Critical Cultural History of Online Games in China, 1995–2015 - Chew, Matthew M. (Games and Culture, 2016)
This study critically assesses the Chinese online games industry through problematizing the creativity of Chinese games. I find that between 1995 and 2001, Chinese online games were mostly developed by amateurs, noncommercial, and considerably creative. Between 2002 and 2005, industrial growth allowed some room for local creativity despite commercialization and dominance of imported games. Current scholarly, business, and media discourses unfairly ignore creativity in these first two periods and yet praise the Chinese game industry’s commercial success since the late 2000s. I challenge these discourses by illustrating that between 2006 and early 2009, a new, ethically dubious, and uniquely Chinese business model emerged, became domestically dominant, and quietly and profoundly impacted on global online game design. From mid-2009 to 2015, there is ongoing corporatization based on the dubious Chinese business model on the one hand, and a reemphasis on creativity motivated by browser and mobile game formats on the other.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Professional Norms and Race in the North American Video Game Industry - Srauy, Sam (Games and Culture, 2019)
This article examines North American (i.e., Canada and the United States) video game developers’ understanding of race, how they construct narratives when they include characters of different races, and some of the pressures that may shape that process. Discourse analyses of semistructured interview texts found that video game developers operate under an internalized pressure to create game narratives that are quickly understandable and, thus, sellable. This pressure is normatively internalized in the profession as an attempt to hedge against market uncertainty. Video game developers, therefore, depend on social beliefs from the “real world” to inform how video game players might receive their games as well as narratives and themes from past texts such as the works of J. R. R. Tolkien. Therefore, this article argues that racism might be enabled because it is believed to be a hedge against market uncertainty.
Keywords: 1-Jeux vidéo; 2-Étude des industries culturelles; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Precarity and Why Indie Game Developers Can’t Save Us from Racism - Srauy, Sam (Television & New Media, 2019)
Exploring issues of labor and inequality at the intersection of AAA and indie sectors, this article interrogates the perception of the indie sector as key to mitigating the production of racializing or racist game content. As developers are central to the industry and the larger games culture, their views reveal how indies are imagined as a privileged site free from economic pressures where racism can be ameliorated. Based on interviews with developers, I argue that the project to redress representational inequities within games is shifted on to indie developers, intensifying their emotional and cultural labor. Indie game developers are imagined as the solution, yet this perspective underestimates the precariousness of independent game production. Economic precariousness may encourage indies to repeat certain patterns of racial representation.
Keywords: 1-Jeux vidéo; 2-Étude des industries culturelles; 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Games With a Continuum: Globalization, Regionalization, and the Nation-State in the Development of China’s Online Game Industry - Jiang, Qiaolei; Fung, Anthony Y.H. (Games and Culture, 2019)
As a case study, this article examines the development of China’s online game industry and how China responds to the forces of globalization. Based on in-depth interviews, ethnographic research, and the analysis of archive documents from the past few years, this study identifies China’s evolving strategy of neo-techno-nationalism. In the Chinese context, this national strategy manipulates technology to create a version of popular nationalism that is both acceptable to and easily censored by the authorities. Therefore, cultural industries that adopt this strategy stand a good chance of prevailing in the Chinese market. This success explains why the regional competitors of Chinese online games—Korean games—are more successful in China than most of their Western counterparts. By providing a snapshot of the current ecology of China’s online game industry, this article also discusses the influence of regional and global forces in a concrete context and argues that the development of China’s online game industry depends more on political factors than economic factors.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

Décentrer l’histoire du jeu vidéo ? - Derfoufi, Mehdi (De l'autre côté, 2018)
Peut-on envisager une autre histoire du jeu vidéo ?
Keywords: 1-Jeux vidéo; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Identités diasporiques; _Nettoyé

Paradoxale légitimation culturelle du jeu vidéo - Derfoufi, Mehdi (De l'autre côté, 2019)
Qualifié parfois de « dixième art », après que les jeux de rôles sur table (comme Donjons & Dragons) eurent commencé à céder du terrain dans les loisirs de la jeunesse à partir du mil…
Keywords: 1-Jeux vidéo; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Identités diasporiques; _Nettoyé

Racisme et jeu vidéo - Derfoufi, Mehdi (Éditions de la Maison des sciences de l'homme, 2021)
En 2007, le monde du jeu vidéo est secoué par une violente polémique au sujet du jeu vidéo Resident Evil 5. Ce dernier est accusé de faire commerce du racisme, en invitant à se glisser dans la peau d'un américain blanc body-buildé, missionné dans une région africaine anonyme, et tuant des dizaines d'hommes et de femmes noires présentées comme de dangereux zombies infectés du virus T. Depuis, la communauté des joueurs et joueuses de jeux vidéo interpelle régulièrement les créateurs et créatrices des jeux sur les questions du racisme et du sexisme.Dans son ouvrage, Mehdi Derfoufi analyse les rapports de force qui structurent l'industrie du jeu vidéo, dévoilant comment le racisme se niche parfois insidieusement au cœur de scénarios de jeux vidéo à succès. Il nous invite à nous questionner. Quels sont les pays qui pèsent sur les milliards d'euros du marché mondial du jeu vidéo ? Qui sont les game designers et auteurs des jeux ? Comment les représentations racistes sont-elles véhiculées à travers les personnageset les imaginaires vidéoludiques ? L'auteur nous dévoile avec brio les logiques racialisantes à l’œuvre au sein d’un marché économique très concurrentiel où des stéréotypes exotisants servent régulièrement à faire vendre un jeu. Il nous montre aussi comment la division internationale du travail et la hiérarchie économico-politique Nord/Sud pèse sur le marché du jeu vidéo et ralentit l’émergence de nouvelles représentations. Pourtant, de nombreux espoirs, notamment dans les pays du Sud participent au renouvellement de la culture geek : face aux violences racistes, la riposte s’organise.
Keywords: 1-Jeux vidéo; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Identités diasporiques; _Nettoyé

Open World Empire: Race, Erotics, and the Global Rise of Video Games - Patterson, Christopher B (New York University Press, 2021)
Seeking ways to understand video games beyond their imperial logics, Patterson turns to erotics to re-invigorate the potential passions and pleasures of play.
OCLC: 1237769915
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

The Race Card: from Gaming Technologies to Model Minorities - Fickle, Tara (New York University Press, 2020)
This book uncovers popular games' key role in the cultural construction of modern racial fictions. It argues that gaming provides the lens, language, and logic - in short, the authority - behind racial boundary making, reinforcing and at times subverting beliefs about where people racially and spatially belong. It focuses specifically on the experience of Asian Americans and the longer history of ludo-Orientalism, wherein play, the creation of games, and the use of game theory shape how East-West relations are imagined and reinforce notions of foreignness and perceptions of racial difference.
OCLC: 1155499741
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

Videojuegos y arte. Primeras manifestaciones de Game Art en Argentina - Jacobo, Mónica (Cuadernos del Centro de Estudios de Diseño y Comunicación Nº41, 2012)
A partir de indagaciones precedentes1 sobre cuestiones como la interactividad y la interfaz presentes en obras realizadas con tecnología digital, este texto realiza una exploración sobre los videojuegos como objetos populares interactivos y sus posibilidades artísticas, procurando contribuir a la construcción de la teoría y práctica en este campo emergente en el contexto local. La perspectiva que articula este trabajo, procura hacer visibles obras de arte producidas en Argentina plausibles de ser ubicadas bajo el campo denominado Game Art, el cual aglutina diferentes producciones en torno al videojuego, reflexionando sobre este como medio y objeto cultural. Esta área de tensiones y cruces vincula a las producciones tradicionales con las digitales, a la práctica denominada Fan Art 2 y al arte culto. Su formación comienza en los últimos años del siglo XX y primeros del Siglo XXI surgiendo esporádicamente en festivales de arte digital e Internet y posteriormente adquiriendo mayor visibilidad con exposiciones temáticas en museos y galerías.
Keywords: 1-Jeux vidéo; 2-Étude des industries culturelles; 3-Amérique du Sud (corpus analysé); 5-Autrice; _Nettoyé; _À analyser; _À nettoyer

The Routledge Companion to Media and Race - Campbell, Christopher (Routledge, 2017)
"The Routledge Companion to Media and Race serves as a comprehensive guide for scholars, students, and media professionals who seek to understand the key debates about the impact of media messages on racial attitudes and understanding. Broad in scope and richly presented from a diversity of perspectives, the book is divided into three sections: first, it summarizes the theoretical approaches that scholars have adopted to analyze the complexities of media messages about race and ethnicity, from the notion of 'representation' to more recent concepts like Critical Race Theory. Second, the book reviews studies related to a variety of media, including film, television, print media, social media, music, and video games. Finally, contributors present a broad summary of media issues related to specific races and ethnicities and describe the relationship of the study of race to the study of gender and sexuality"–Provided by publisher.
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Épistémologies autochtones; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; _À analyser; _À nettoyer; _À vérifier-Cinéma; _À vérifier-Histoire de l'art; _À vérifier-Télé

The Routledge Companion to Media Studies and Digital Humanities - Sayers, Jentery (Taylor and Francis, 2018)
"Although the fields of media studies and digital humanities are both well established, their overlaps have not been examined in depth. This comprehensive collection fills that gap, giving students, scholars, and media studies practitioners a cutting-edge guide to understanding the array of methodologies and projects operating at the intersection of digital humanities, computing, and culture. Topics covered include: networks; interfaces; media and culture at scale; procedures, programming, code; memory, digitization, and new media; and hacking, queering, and bending."–Provided by publisher
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Humanités numériques; 2-Épistémologies autochtones; 2-Étude des industries culturelles; 2-Étude des représentations; 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé; _À analyser; _À nettoyer; _À vérifier-Histoire de l'art; _À vérifier-Télé

Game Devs & Others: Tales from the Margins - DePass, Tanya (CRC Press, 2018)
Game Devs & Others: Tales from the Margins tell the true stories of life in the industry by people of color, LGBTQIA and other marginalized identities. This collection of essays give people a chance to tell their stories and to let others know what life on the other side of the screen is like when you’re not part of the supposed “majority”. Key Features This book is perfect for anyone interested in getting into the games industry who feels they have a marginalized identity For those who wish to better diversify their studio or workplace who may or may not have access to individuals that could or would share their stories about the industry Includes initiatives aimed at diversifying the industry that have a positive or negative impact on the ongoing discussions Coverage of ajor news items about diversity, conferences aimed at or having diversity at its core of content and mission are discussed Included essays are written with as little game dev specific jargon as possible, makeing it accessible to people outside the industry as well as those in the scene but that may not have all the insider lingo
Google-Books-ID: Gv5cDwAAQBAJ
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Méthodologie de recherche décoloniale; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice LGBTQ+; 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; 5-Créateur.rice LGBTQ+; 5-Créateur.rice PANDC; 5-Créateur.rice autochtone; 5-Créateur.rice noir.e; 5-Créatrice; 5-Identités diasporiques; _Nettoyé

Digital Dispossessions: the Importance of Regional Specificity and Sovereign Spaces to Video Game Representations of Native American Cultural Heritage - Bird, Ashlee (Studia Neophilologica, 2021)
Indigenous peoples and their cultural heritages, their ways of knowing and living, are tied to land. As Mishuana Goeman states,“Land is foundational to people’s cultural practices, and if we define culture as meaning making rather than as differentiation and isolation in a multicultural neoliberal model, thanby thinking through land as a meaning-making process rather than a claimed object, the aspiration of Native people are apparent and clear,” (Goeman, 73).Goeman asserts here that land is not limited to physical space, and that land locates a group of people physically, culturally, spiritually, intellectually,etc. and provides them with both an internal and external locus of understanding for and within broader society. When digital representations of Indigenous peoples are completely removed from any meaningful connection to their land, anerasure of culture occurs. Moreover, the physical removal of Indigenous peoples from the virtual representations of their lands is another form of dispossession and the enactment of digital Manifest Destiny. This paperutilizes a decolonial Indigenous framework to analyze the dispossessions that take place within the digital realm of the video game, why they occur so frequently, and why they are so harmful.
_eprint: https://doi.org/10.1080/00393274.2021.1916995
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; _Nettoyé

Examining the Intersection of Race and Gender in Video Game Advertising - Behm-Morawitz, Elizabeth (Journal of Marketing Communications, 2017)
Women and racial/ethnic minorities account for a growing percentage of video game players in the USA. The economic future of the video game industry may, in part, depend on the industry's ability to adapt marketing efforts to appeal to the growing female and racial/ethnic markets. Contrary to these efforts, however, is advertisers' reliance on stereotypes in advertisements to quickly establish a common understanding and wide appeal to a mass audience. This study investigates how race and gender intersect in the stereotypical character depictions used to market video games to consumers. A systematic content analysis was carried out of 383 US magazine advertisements of console, mobile, and PC video games. Stereotyping and intersectionality literatures were used as theoretical guides for this research. Findings reveal that the marketing of video games in the USA upholds some longstanding media stereotypes of minorities and women, including that of the White male hero, submissive sexualized female, Asian ninja, and deviant Black male. The potential social and economic implications of the video game industry's reliance on character stereotypes for the marketing of video games are discussed.
_eprint: https://doi.org/10.1080/13527266.2014.914562
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; _Nettoyé

Indigenous Representations and the Impacts of Video Games Media on Indigenous Identity - Lagace, Naithan (University of Manitoba, 2018)
This thesis analyzes and discusses the complexities of digital representations involving Indigenous peoples through video games. Connecting both Game Theory and Native Studies, I analyze how digital games incorporate identity, culture, and relationships in diverse and intellectual ways and provide new spaces for Indigenous agency and semiotics. Beginning with an analysis of several historical and negative representations of Indigenous peoples, I then compare those tropes to projects within today’s environment and mainstream video game companies, independent companies, and educational service providers. I assert that while some digital media representations of Indigenous cultures are stereotypical and problematic, others facilitate a sense of cultural continuance and survivance. Lastly, some video games display both stereotypical and cultural continuance within them.
Accepted: 2019-01-10T21:28:57Z
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Épistémologies autochtones; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Imagining Indigenous Digital Futures: An Afterword - Raheja, Michelle (Studies in American Indian Literatures, 2017)
In lieu of an abstract, here is a brief excerpt of the content: As I sit writing in my kitchen while the forces of the U.S. military state are brought to bear on thousands of Standing Rock water stewards and land protectors and their allies in Cannonball, North Dakota, I consider how this sail special issue on digital Indigenous studies not only represents a collection of essays about the critical work Indigenous women are performing in their various digital projects but also illustrates that these online “Indigenous territories” (Hearne), crafted on social media platforms such as Twitter and Facebook, save lives. Every single day since the protectors first gathered to oppose the proposed 1,170-mile Dakota Access pipeline (a project that would potentially contaminate the Missouri watershed and the Ogallala Aquifer and desecrate Dakota sacred sites), digital independent and social media have constantly covered the story. At least 1.3 million Facebook users checked in virtually at Oceti Sakowin and other Indigenous camps and communities to ensure that support presence is recognized, while the world monitors the presence of the military and police force gathering at the construction site to curb further violence. The Standing Rock gathering offers hope to networked Indigenous youth, a demographic between three and ten times as likely to commit suicide than the national average peer rate. The Nodapl action in the Indigenous imaginary is an invitation to stand at the front lines of a global movement to protect water and land resources for all living beings on this planet and to draw attention to and support those whose lives and ways of being are in peril through overt military action and consequential environmental destruction. It is also an occasion, in the words of Jolene Rickard, “to invest in the apparatus of the imagination” (Bernardin). One need only look at the online art, handwritten signs, and logos representing #nodapl, #standingrock, [End Page 172] #waterislife, and #rezpectourwater to see the ways in which Indigenous artists are creatively and powerfully envisioning this movement, most often immersed with work that features strong images of Native women and girls, the community backbone and life force. Or we need only view digital videos like computer animator and artist Joseph Erb’s black-and-red graphic history of Standing Rock, “Mni Wiconi / Water Is Life” (https://www.youtube.com/watch?v=kXoy5lzpjiM), and first-person game platforms like Elizabeth LaPensée’s Thunderbird Strike, which extend the conversations at Standing Rock to the struggles over Enbridge’s Alberta tar sands pipeline and fracking practices as players work to undo and prevent further environmental degradation. Following Idle No More’s digital and geospatial (re)articulation of Indigenous territories, we are now living and loving and hoping in this historic moment as new ways of relating to one another and living in deep connection with the land and all its forms of life are being physiologically, intellectually, and spiritually forged at the geospatial confluence of the Missouri and Cannonball Rivers. They are being forged as well through the confluences of digital rivers on our electronic devices and in our online conversations about the beauty and devastation of the events that are unfolding in Standing Rock. Susan Bernardin’s essay in this issue on Heid E. Erdrich’s “Pre-Occupied” considers the meaning of rivers to Native peoples and contends that images of waterways, particularly the Mississippi, are mobilized “to make visible the continuing claims of this and other imperiled riverine systems.” In her introduction, Joanna Hearne asks us, “How might such an intersection of digital and Indigenous specificities take place in a way that is ‘native to the device’; that is, how might Indigenous specificity be embedded in shared platforms that are therefore central to all of our digital lives?” The essays in this special issue respond to this question by theorizing digital media in fresh and innovative ways. Many of us teach digital humanities courses or classes with strong digital media content, but we lack the language for critically engaging this new field on its own terms as it intersects, extends, and radically reconceptualizes more familiar research areas such as cinema studies, Indigenous / Native American studies, communication, literature, art, and history.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Humanités numériques; 2-Épistémologies autochtones; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Critical Protocols in Indigenous Gamespace - Miner, Joshua D. (Games and Culture, 2022)
This article examines Indigenous video games that critique mainstream environmental politics at the level of mechanics. An analysis of video games’ influences on ecological values requires looking beyond the representational to the mechanical relationships between player and software. As a cultural–computational medium, video games are embedded with ethics of interaction that inflect this representational dimension by requiring that players generate the text as participant. With the recent visibility of Indigenous rights movements, developers have embedded Indigenous cultural protocols in the mechanical interactions (or technical protocols) of gameplay. In the context of critique, their integration produces “critical protocols,” configurations of gamic action that encourage players to evaluate their treatment of real-world environments. Critical protocols emerge between the technical and cultural, where scripts for interaction in algorithmic spaces intervene in affirmative game design and work as an analog beyond the game. Indigenous developers call for new ways of computing and critiquing settler digitality through play. These games aim toward representational as well as computational sovereignty.
Keywords: 1-Jeux vidéo; 2-Humanités numériques; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice autochtone; _Nettoyé

When Rivers Were Trails: Cultural Expression in an Indigenous Video Game - LaPensée, Elizabeth (International Journal of Heritage Studies, 2021)
When Rivers Were Trails is a 2D adventure game wherein The Oregon Trail meets Where the Water Tastes Like Wine through an Indigenous lens. The game depicts a myriad of cultures during the player’s journey from Minnesota to California amidst the impact of land allotment in the 1890s. Initiated by the Indian Land Tenure Foundation, the game was developed in collaboration with the Games for Entertainment and Learning Lab at Michigan State University thanks to support from the San Manuel Band of Mission Indians and the many Indigenous creatives who contributed design, art, music, and writing. Uniquely, When Rivers Were Trails is a sovereign game, meaning that it was directed and informed by Indigenous creatives who maintained the role of final decisions during development. Merging design research and close reading methods, this study sets out to describe the game’s design, development process in regards to the game writing, and the resulting themes which emerged as a result of engaging Indigenous writers in self-determined representations.
_eprint: https://doi.org/10.1080/13527258.2020.1746919
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Humanités numériques; 2-Pédagogie décoloniale; 2-Épistémologies autochtones; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Indie and Dojin Games : a Multilayered Cross-Cultural Comparison - Fiadotau, Mikhail (Gamevironments, 2019)
The article provides a comparative account of two paradigms of independent videogame production: the Japanese dojin (doujin) games and the increasingly global indie games. Through a multilayered analysis, it expounds the conceptual metaphors associated with indie and d jin games, traces the two movements respective histories, situates them in wider media environments, and compares their characteristic traits.
Accepted: 2020-03-25T23:30:23Z
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Europe (lieu de production du savoir); _Nettoyé

Interview with Deyfou-lah Sani Bah-Traore on the Togolese Game Origin - the Rise of Dzitri - Kienzl, Lisa; Bah-Traore, Deyfou-lah Sani (Gamevironments, 2019)
In the Togelese game Origin - the Rise of Dzitri that was developed in Lome, the character Edoh takes you on a journey to historic places in the city to revive the spirit of Dzitri. Deyfou-lah Sani Bah-Traore, programmer and game developer, spoke with Lisa Kienzl about his and his Teammate s work on Origin - the Rise of Dzitri
Accepted: 2020-03-25T23:30:30Z
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 4-Afrique (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Autrice; 5-Créateur.rice PANDC; 5-Créateur.rice noir.e; _Nettoyé

Interview with Mira Wardhaningsih from StoryTale Studios on the Indonesian Horror Game Pamali - Trattner, Kathrin; Wardhaningsih, Mira (Gamevironments, 2019)
An interview by Kathrin Trattner with Mira Wardhaningsih, Cultural Content Director from StoryTale Studios about the game Pamali
Accepted: 2020-03-25T23:30:30Z
Keywords: 1-Jeux vidéo; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Autrice; 5-Créateur.rice PANDC; 5-Créatrice; _Nettoyé

Round Table Discussion on Nation(alism), Identity and Video Gaming with Megan Condis, Marijam Didzgalvyt , Georg Hobmeier and Souvik Mukherjee - Trattner, Kathrin; Condis, Megan; Didzgalvyt, Marijam; Hobmeier, Georg; Mukherjee, Souvik; Kienzl, Lisa (Gamevironments, 2019)
Questions of nation and identity not only concern multiple aspects of video games, their production, and their consumption, but also require further and manifold discussion from different perspectives. In an effort to bring together voices from different fields that engage with video games and gaming practices from various perspectives, this virtual round table discussion attempts to open up the conversation beyond the realms of academia. Kathrin Trattner and Lisa Kienzl talked to Megan Condis, Marijam Didzgalvyt , Georg Hobmeier and Souvik Mukherjee about how concepts such as nation(alism) and identity impact video game representations, the gaming industry, and online gaming cultures in numerous ways.
Accepted: 2020-03-25T23:30:29Z
Keywords: 1-Jeux vidéo; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

Interview With Ryan Sumo, Lead Artist/Business Developer At Squeaky Wheel Studio - Radde-Antweiler, Kerstin; Sumo, Ryan (Gamevironments, 2018)
Interview with Ryan Sumo, Lead Artist/Business Developer at Squeaky Wheel Studio
Accepted: 2020-03-25T23:30:10Z
Keywords: 1-Jeux vidéo; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Autrice; 5-Créateur.rice PANDC; _Nettoyé

Interview With Ben Joseph P. Banta, Founder Of Ranida Games - Radde-Antweiler, Kerstin; Banta, Ben Joseph P. (Gamevironments, 2018)
Interview With Ben Joseph P. Banta, Founder Of Ranida Games
Accepted: 2020-03-25T23:30:10Z
Keywords: 1-Jeux vidéo; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Autrice; 5-Créateur.rice PANDC; _Nettoyé

Interview With The Creator Of Boo! Dead Ka! Game - Radde-Antweiler, Kerstin; Prieto, Kurt (Gamevironments, 2018)
Interview with With Kurt Prieto, Games Designer Of Boo! Dead Ka! Game
Accepted: 2020-03-25T23:30:10Z
Keywords: 1-Jeux vidéo; 2-Humanités numériques; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Autrice; 5-Créateur.rice PANDC; _Nettoyé

An Ethnoludography of the Game Design Industry in Kathmandu, Nepal - Grieve, Gregory P. (Gamevironments, 2018)
What counts as the field site when researching Nepali video game developers? Concentrating on the company Arcube Games and Animation, in the summer of 2017 I used the ethnoludographic method to research game development in the Kathmandu Valley. I recorded my findings in field notes, photographs, written documents and other material culture. My usual ethnographic method developed in two ways. First, I engaged in ludography, a humanistic qualitative method for interpreting gaming. Second, Nepal proved not to be an isolated location, but rather a vortex of global flows. I found that in the Kathmandu valley these flows are often focused on a fantasy of Shangri-La that poses Nepal as an underdeveloped traditional nation, full of picturesque poverty, and over-determined with religious culture, but blessed with beautiful Himalayan landscapes.
Accepted: 2020-03-25T23:30:09Z
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Geemu On! A Preliminary Study Of Indie And Doujin Game Development In Japan - Helland, Christopher (Gamevironments, 2018)
This paper is a brief summary of a preliminary exploration of certain aspects of independent video game development in Japan. Initial interviews were conducted with researchers and indie game developers over a two-week period in Tokyo. Independent game developers from Kamakura were also interviewed as part of the research. Initial fieldwork was geared primarily toward doujin level game development and distribution. My key research question focused upon the religious and spiritual dimensions of doujin games. However, after conducting interviews it became clear that developers did not consider the Western frame or classification of religion and spirituality in their development but rather incorporated aspects of tradition, culture and values within their work.
Accepted: 2020-03-25T23:30:09Z
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Interview with Zainuddeen Fahadh, Founder of Ogre Head Studio - Zeiler, Xenia; Zainuddeen, Fahadh (Gamevironments, 2018)
Interview with Zainuddeen Fahadh, Founder of Ogre Head Studio, Hyderabad, India
Accepted: 2020-03-25T23:30:09Z
Keywords: 1-Jeux vidéo; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Autrice; 5-Créateur.rice PANDC; _Nettoyé

Interview with Avinash Kumar, Creative Director & Co-Founder, Quicksand Design Studio - Zeiler, Xenia; Kumar, Avinash (Gamevironments, 2018)
Interview with Avinash Kumar, Creative Director & Co-Founder, Quicksand Design Studio, India.
Accepted: 2020-03-25T23:30:09Z
Keywords: 1-Jeux vidéo; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Autrice; 5-Créateur.rice PANDC; _Nettoyé

Interview with Avichal Singh, Founder and Game Designer of Nodding Heads Games - Zeiler, Xenia; Singh, Avichal (Gamevironments, 2018)
Interview with Avichal Singh, Founder and Game Designer of Nodding Heads Games, Pune, India.
Accepted: 2020-03-25T23:30:09Z
Keywords: 1-Jeux vidéo; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Autrice; 5-Créateur.rice PANDC; _Nettoyé

Interview with Satyajit Chakraborty, Founder of Flying Robot Studios, Kolkata, India - Zeiler, Xenia; Chakraborty, Satyajit (Gamevironments, 2018)
Accepted: 2020-03-25T23:30:08Z
Keywords: 1-Jeux vidéo; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Autrice; 5-Créateur.rice PANDC; _Nettoyé

Video Game Development In Asia: Voices From The Field - Grieve, Gregory P.; Radde-Antweiler, Kerstin; Zeiler, Xenia; Helland, Christopher (Gamevironments, 2018)
Introduction to the gamevironments Special Issue Video Game Development in Asia: Voices from the Field .
Accepted: 2020-03-25T23:30:09Z
Keywords: 1-Jeux vidéo; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Autrice; _Nettoyé

Video Game Development in Asia : a Research Project on Cultural Heritage and National Identity - Grieve, Gregory P.; Helland, Christopher; Radde-Antweiler, Kerstin; Zeiler, Xenia (Gamevironments, 2017)
A report of the 2017 collaborative research project Video Game Development in Asia. Cultural Heritage and National Identity.
Accepted: 2020-03-25T23:29:51Z
Keywords: 1-Jeux vidéo; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Autrice; _Nettoyé

Interview with Shailesh Prabhu, Indian Game Designer - Prabhu, Shailesh (Game Studies, 2016)
Interview with the Indian Game Designer Shailesh Prabhu about his game Sky Sutra.
Accepted: 2020-03-25T23:29:20Z
Keywords: 1-Jeux vidéo; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Créateur.rice PANDC; _Nettoyé

The Indian Indie Game Development Scene - History and Cultural Heritage as Game Themes - Zeiler, Xenia (Gamevironments, 2016)
While the Indian indie game development scene is still relatively young, it has already lived through big changes. Like in many regions worldwide, indie game developers in India have to negotiate between practical issues, for example regarding market requirements and expectations, and committed ambitions, for example regarding creative aspirations in art design and game content. On the one hand and in order to persist in the ever extending industry, they need to acknowledge mainstream wants and practical demands from especially (though not exclusively) the Indian game market which at present is characterized by an overall dominance of mobile card and casino games. On the other hand, we see that especially Indian indie developers increasingly reflect on the role of Indian cultural heritage (including elements from history, architecture, music, etc.) for India produced games. This turn to own roots, to implement Indian cultural and historical heritage in games, is now visible in a number of games which have been recently Greenlit on Steam and are in the final production phases, such as Asura (2017 forthc.), Antariksha Sanchar (2017 forthc.), and others.
Accepted: 2020-03-25T23:29:32Z
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Europe (lieu de production du savoir); 5-Autrice; _Nettoyé

Imperialism and Fascism Intertwined. A Materialist Analysis of the Games Industry and Reactionary Gamers - Hammar, Emil Lundedal (Gamevironments, 2020)
This article paves way for a materialist analysis of the games industry as 21st century imperialism that is economically and culturally structured to cultivate anti-democratic norms that lead to fascist movements against those who question or seek to change the status quo. While much research has studied the politics of reactionary movements in gaming cultures, few have paid attention to the relation between the games industry as part of an imperialist economic system, the chauvinistic ideals symptomized in their cultural products, and the reactionist consumer audiences they attract and cultivate. As I argue, the economic structure of the industry as 21st century imperialism leads to perpetual anti-democratic crises that are maintained by reactionary forces that cultivate, attract, and form fascist grassroots organization. To conceptualize this dynamic, I invoke the labor aristocracy theory as suggested by Friedrich Engels and V.I. Lenin. This theory helps highlight the material basis from which consumers of digital games are bribed to become ideologically aligned with the chauvinism that the imperialist nature of the games industry is justified by. I also invoke W.E.B. Du Bois’ concept of a public and psychological wage to highlight the chauvinistic tendencies that the games industry cultivates via their products and marketing, in which the lack of democratic and equitable representation provides the reactionary consumers a sense of superiority. Together, these approaches account for the economic and cultural bases of both the games industry and its reactionary consumers. By anchoring my analysis in critical theories on imperialism and race, the article identifies the root causes of organized harassment and chauvinism in game cultures, as well as how the industry as 21st century imperialism benefits from and is protected by these forces of reaction.
Accepted: 2020-12-29T10:24:13Z
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 4-Europe (lieu de production du savoir); _Nettoyé

Playing with Race: The Ethics of Racialized Representations in E-Games - Chan, Dean (Internaitonal Review of Information Ethics, 2005)
Questions about the meanings of racialized representations must be included as part of developing an ethical game design practice. This paper examines the various ways in which race and racial contexts are represented in a selected range of commercially available e-games, namely war, sports and action-adventure games. The analysis focuses on the use of racial slurs and the contingencies of historical re-representation in war games; the limited representation of black masculinity in sports games and the romanticization of ‘ghetto play’ in urban street games; and the pathologization and fetishization of race in ‘crime sim’ action-adventure games such as True Crime: Streets of LA. This paper argues for, firstly, a continuous critical engagement with these dominant representations in all their evolving forms; secondly, the necessary inclusion of reflexive precepts in e-games development contexts; and thirdly, the importance of advocating for more diverse and equitable racialized representations in commercial e-games.
Keywords: 1-Jeux vidéo; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Lions & Jackals: the Politics of Far Cry 2 - Albor, Jorge (Well Played 2.0: Video Games, Value and Meaning, 2010)
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); _Nettoyé

Gaming: essays on algorithmic culture - Galloway, Alexander R. (University of Minnesota Press, 2006)
Considers the video game as a distinct cultural form that demands a unique interpretive framework. This book analyzes video games as something to be played rather than as texts to be read, and traces how the "algorithmic culture" created by video games intersects with theories of visuality, realism, allegory, and the avant-garde.
Section: 1 v. (XIII-143 p.) : illustrations ; 22 cm
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

The International Encyclopedia of Media Studies: Media History and the Foundations of Media Studies - Valdivia, Angharad N.; Nerone, John C.; Mayer, Vicki; Mazzarella, Sharon R.; Parameswaran, Radhika E.; Scharrer, Erica; Darling-Wolf, Fabienne; Gates, Kelly (Wiley-Blackwell, 2013)
Keywords: 1-Cinéma; 1-Jeux vidéo; 1-TV; 2-Analyses formalistes; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé; _À analyser; _À nettoyer; _À vérifier-Cinéma; _À vérifier-Télé

Racial Diversity in Indie Games: Patterns, Challenges, and Opportunities - Passmore, Cale J.; Yates, Rowan; Birk, Max V.; Mandryk, Regan L. (Extended Abstracts Publication of the Annual Symposium on Computer-Human Interaction in Play, 2017)
Although gamers of color constitute a large part of the digital gaming player base in the US, they are systematically and enormously underrepresented by in-game characters in AAA titles. To extend these findings to indie games, we examine 80 titles and show that the pattern of lack of racial diversity holds. We discuss implications for the industry and players, and present challenges that must be addressed to increase diversity in racial representations of characters in games.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; _Nettoyé

Gender, Race, and Class in Media a Critical Reader - Dines, Gail.; Humez, Jean M. (SAGE Publications, 2015)
Incisive analyses of mass media - including such forms as talk shows, MTV, the Internet, soap operas, television sitcoms, dramatic series, pornography, and advertising-enable this provocative third edition of Gender, Race and Class in Media to engage students in critical mass media scholarship. Issues of power related to gender, race, and class are integrated into a wide range of articles examining the economic and cultural implications of mass media as institutions, including the political economy of media production, textual analysis, and media consumption. Throughout, Gender, Race and Class in Media examines the mass media as economic and cultural institutions that shape our social identities, especially in regard to gender, race, and class.
Section: 1 vol. (XIV-761 p.) : ill. ; 26 cm
Keywords: 1-Cinéma; 1-Jeux vidéo; 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé; _À analyser; _À nettoyer; _À vérifier-Cinéma; _À vérifier-Télé

Looking for Leroy: Illegible Black Masculinities - Neal, Mark Anthony (New York University Press, 2013)
Mark Anthony Neal’s Looking for Leroy is an engaging and provocative analysis of the complex ways in which black masculinity has been read and misread through contemporary American popular culture. Neal argues that black men and boys are bound, in profound ways, to and by their legibility. The most “legible” black male bodies are often rendered as criminal, bodies in need of policing and containment. Ironically, Neal argues, this sort of legibility brings welcome relief to white America, providing easily identifiable images of black men in an era defined by shifts in racial, sexual, and gendered identities. Neal highlights the radical potential of rendering legible black male bodies—those bodies that are all too real for us—as illegible, while simultaneously rendering illegible black male bodies—those versions of black masculinity that we can’t believe are real—as legible. In examining figures such as hip-hop entrepreneur and artist Jay-Z, R&B Svengali R. Kelly, the late vocalist Luther Vandross, and characters from the hit HBO series The Wire, among others, Neal demonstrates how distinct representations of black masculinity can break the links in the public imagination that create antagonism toward black men. Looking for Leroy features close readings of contemporary black masculinity and popular culture, highlighting both the complexity and accessibility of black men and boys through visual and sonic cues within American culture, media, and public policy. By rendering legible the illegible, Neal maps the range of identifications and anxieties that have marked the performance and reception of post-Civil Rights era African American masculinity.
Google-Books-ID: sKRFmvIVcEIC
Keywords: 2-Étude des industries culturelles; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; _Nettoyé; _À analyser; _À nettoyer; _À vérifier-Cinéma; _À vérifier-Histoire de l'art; _À vérifier-Télé

Game over: Asian Americans and Video Game Representation - Phi, Thien-bao Thuc (Transformative Works and Cultures, 2009)
Even video games by Asian creators tend to depict primarily white characters or reference Asian stereotypes such as kung fu fighters or yakuza thugs. Games depicting the Vietnam war are particularly troubling for Asian players expected to identify with white characters. As the game industry continues to expand, its representation of Asians and Asian Americans must change.
Keywords: 1-Jeux vidéo; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Crash Override: How Gamergate (Nearly) Destroyed My Life, and How We Can Win the Fight Against Online Hate - Quinn, Zoë (PublicAffairs, 2017)
You've heard the stories about the dark side of the internet – hackers, #gamergate, anonymous mobs attacking an unlucky victim, and revenge porn – but they remain just that: stories. Surely these things would never happen to you. Zoe Quinn used to feel the same way. She is a video game developer whose ex-boyfriend published a crazed blog post cobbled together from private information, half-truths, and outright fictions, along with a rallying cry to the online hordes to go after her. They answered in the form of a so-called movement known as #gamergate–they hacked her accounts; stole nude photos of her; harassed her family, friends, and colleagues; and threatened to rape and murder her. But instead of shrinking into silence as the online mobs wanted her to, she raised her voice and spoke out against this vicious online culture and for making the internet a safer place for everyone. In the years since #gamergate, Quinn has helped thousands of people with her advocacy and online-abuse crisis resource Crash Override Network. From locking down victims' personal accounts to working with tech companies and lawmakers to inform policy, she has firsthand knowledge about every angle of online abuse, what powerful institutions are (and aren't) doing about it, and how we can protect our digital spaces and selves.Crash Override offers an up-close look inside the controversy, threats, and social and cultural battles that started in the far corners of the internet and have since permeated our online lives. Through her story – as target and as activist – Quinn provides a human look at the ways the internet impacts our lives and culture, along with practical advice for keeping yourself and others safe online.
Google-Books-ID: gpvUDQAAQBAJ
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Étude des industries culturelles; 4-Europe (lieu de production du savoir); 5-Autrice; 5-Créatrice; _Nettoyé

Learning Race and Ethnicity: Youth and Digital Media - Everett, Anna (The MIT Press, 2008)
An exploration of how issues of race and ethnicity play out in a digital media landscape that includes MySpace, post-9/11 politics, MMOGs, Internet music distribution, and the digital divide.
Section: 1 v. (IX-197 p.) : illustrations ; 27 cm
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; _Nettoyé

Featuring Females: Feminist Analyses of Media - Cole, Ellen; Daniel, Jessica Henderson (American Psychological Association, 2005)
"Featuring Females analyzes the portrayals of women in a variety of outlets, including reality television shows, films, print and electronic news programming, magazines, video games, and commercial advertising. A highly esteemed group of scholars and researchers provides informed, original psychological study, and their thought-provoking findings address the ways in which aging, race/ethnicity, body image, gender roles, sexual orientation and relationships, and violence are treated in the media. Featuring Females is a diverse volume, exploring images and characterizations of women young and old and inspiring discussion of the effects that these representations have on girls, women, and society at large"–
OCLC: 57754311
Keywords: 1-Jeux vidéo; 2-Analyses formalistes; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; 5-Créateur.rice PANDC; 5-Créateur.rice noir.e; 5-Créatrice; _Nettoyé; _À analyser; _À vérifier-Cinéma; _À vérifier-Télé

Not a Hater, Just Keepin' It Real The Importance of Race- and Gender-Based Game Studies - Leonard, David J. (Games and Culture, 2006)
Notwithstanding the presence of extreme racialized tropes within the world of videogames, public discourses continue to focus on questions of violence, denying the impor-tance of games in maintaining the hegemonic racial order. Efforts to exclude race (andintersections with gender, nation, and sexuality) from public discussions through its era-sure and the acceptance of larger discourses of colorblindness contribute to a problematicunderstanding of video games and their significant role in contemporary social, political,economic, and cultural organization. How can one truly understand fantasy, violence,gender roles, plot, narrative, game playability, virtual realities, and the like without ex-amining race, racism, and/or racial stratification—one cannot. This article challengesgame studies scholars to move beyond simply studying games to begin to offer insightand analysis into the importance of race and racialized tropes within virtual reality andthe larger implications of racist pedagogies of video games in the advancement of Whitesupremacy.
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Méthodologie de recherche décoloniale; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Playing to Win: Sports, Video Games, and the Culture of Play - Brookey, Robert Alan; Oates, Thomas Patrick (Indiana University Press, 2015)
In this era of big media franchises, sports branding has crossed platforms, so that the sport, its television broadcast, and its replication in an electronic game are packaged and promoted as part of the same fan experience. Editors Robert Alan Brookey and Thomas P. Oates trace this development back to the unexpected success of Atari's Pong in the 1970s, which provoked a flood of sport simulation games that have had an impact on every sector of the electronic game market. From golf to football, basketball to step aerobics, electronic sports games are as familiar in the American household as the televised sporting events they simulate. This book explores the points of convergence at which gaming and sports culture merge.
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Autrice; _Nettoyé

Kill the Overseer!: the Gamification of Slave Resistance - Lauro, Sarah Juliet. (University of Minnesota Press, 2020)
Profiles and problematizes digital games that depict Atlantic slavery and "gamify" slave resistance. In videogames emphasizing plantation labor, the player may choose to commit small acts of resistance like tool-breaking or working slowly. Others dramatically stage the slave's choice to flee enslavement and journey northward, and some depict outright violent revolt against the master and his apparatus. This work questions whether the reduction of a historical enslaved person to a digital commodity in games such as Mission US, Assassin's Creed, and Freedom Cry ought to trouble us as a further commodification of slavery's victims, or whether these interactive experiences offer an empowering commemoration of the history of slave resistance.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; _Nettoyé

Feminism in Play - Gray, Kishonna L.; Voorhees, Gerald; Vossen, Emma (Palgrave Macmillan, 2018)
Feminism in Play focuses on women as they are depicted in video games, as participants in games culture, and as contributors to the games industry. This volume showcases women's resistance to the norms of games culture, as well as women's play and creative practices both in and around the games industry. Contributors analyze the interconnections between games and the broader societal and structural issues impeding the successful inclusion of women in games and games culture. In offering this framework, this volume provides a platform to the silenced and marginalized, offering counter-narratives to the post-racial and post-gendered fantasies that so often obscure the violent context of production and consumption of games culture.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé

Woke Gaming: Digital Challenges to Social Injustice - Gray, Kishonna L.; Leonard, David J. (University of Washington Press, 2018)
From #Gamergate to the daily experiences of marginalization among gamers, gaming is entangled with mainstream cultures of systematic exploitation and oppression. Whether visible in the persistent color line that shapes the production, dissemination, and legitimization of dominant stereotypes within the industry itself, or in the dehumanizing representations often found within game spaces, many video games perpetuate injustice and mirror the inequities and violence that permeate society as a whole. Drawing from the latest research and from popular games such as World of warcraft and Tomb raider, Woke gaming examines resistance to spaces of violence, discrimination, and microaggressions in gaming culture. The contributors of these essays identify strategies to detox gaming culture and orient players toward progressive ends, illustrating the power and potential of video games to become catalysts for social justice
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Méthodologie de recherche décoloniale; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé

Japanese Culture Through Videogames - Hutchinson, Rachael (Routledge/Taylor & Francis Group, 2019)
"Examining a wide range of Japanese videogames, including arcade fighting games, PC-based strategy games and console JRPGs, this book assesses their cultural significance and shows how gameplay and context can be analyzed together to understand videogames as a dynamic mode of artistic expression. Well-known titles such as Final Fantasy, Metal Gear Solid, Street Fighter and Katamari Damacy are evaluated in detail, showing how ideology and critique are conveyed through game narrative and character design as well as user interface, cabinet art, and peripherals. This book also considers how Japan' has been packaged for domestic and overseas consumers, and how Japanese designers have used the medium to express ideas about home and nation, nuclear energy, war and historical memory, social breakdown and bioethics. Placing each title in its historical context, Hutchinson ultimately shows that videogames are a relatively recent but significant site where cultural identity is played out in modern Japan. Comparing Japanese videogames with their American counterparts, as well as other media forms, such as film, manga and anime, Japanese Culture Through Videogames will be useful to students and scholars of Japanese culture and society, as well as Game Studies, Media Studies and Japanese Studies more generally."– Provided by publisher.
Keywords: 1-Jeux vidéo; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Europe (lieu de production du savoir); 5-Autrice; _Nettoyé

Games Studies India Adda #6: Zahra Rizvi - Game Studies India Adda (Game Studies India Adda, 2021)
Playing Dystopia: Searching for the Neganthropocene in Papers, Please and Orwell The way we play games and the way games play us is constantly changing. The physical shrinking of space can no longer be compensated by expansive gamescapes which otherwise provided a reprieve from diminishing access to space in 20th and 21st century childhood (Mayra, An Introduction to Game Studies). Gamescapes, increasingly, are becoming neo-explorations of “other people simulators” characterized by a suffocating hypernearing of the experience of the dystopia (Lucas Pope). Often ‘mundane’ mirrors of real-life situations, these dystopian games place the player in movement-limiting, choice-limiting challenging scenarios from where a fulfilling ending is more often than not impossible. I look at two of these dystopian games that offer covertly disruptive gameplay through alienating, often disembodied, simulation as a strategy for playing dystopia: Lucas Pope’s Papers, Please and Osmotic Studios’ Orwell. Closely engaging with issues of surveillance, digital governance, neurotechnology, illegal profiling, and ultimately, survival in a dystopia of technics, these games with their multiple endings caused by the smallest, seemingly most insignificant of differences in gameplay become crucial in their playing out of the possibilities of the neganthropocene.
Keywords: 1-Jeux vidéo; 2-Humanités numériques; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Games Studies India Adda Talk #4: Poonam Chowdhury - Game Studies India Adda (Game Studies India Adda, 2021)
Thatgamecompany’s 'Journey' (2012) is a videogame like no other. This serene atmospheric game came out at a time when fast-paced, aggressive, AAA games were (and still are) the norm. Soon after the game’s release in 2012, thatgamecompany’s courage and hard work started getting the appreciation it deserved. 'Journey' has won several ‘Game of the Year’ awards and received several other awards and nominations, including a ‘Best Score Soundtrack for Visual Media’ nomination for the 2013 Grammy Awards. For this Game Studies India Adda Talk, I will be discussing (read: gushing over) this game’s brilliant visual and auditory art, wordless storytelling techniques, and one-of-a-kind multiplayer experience. Please join me on this talk and let's take a ‘journey’ like no other. Pun intended. Thank you and I hope you all have a wonderful new year. 🙂 Here’s the game trailer: https://www.youtube.com/watch?v=Ie4iz...
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Amérique du Nord (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

Games Studies India Adda Talk #3 The vanishing Curator - Game Studies India Adda (Game Studies India Adda, 2020)
Playing back to the Empire, in videogames, is rife with tensions. The imperialist sentiment inherent in reverse-colonist discourse featured in most strategy-based videogames like Europa Universalis IV, where the player could conquer Europe playing for the Marathas, has been noted by Souvik Mukherjee (2017) as playing into the colonial logic while futilely trying to challenge it. Studio Oleomingus, an Indian two-man game studio, is one of the few involved in a different experiment. Their mythical game Somewhere, chronicling a postmodernist search for identity and narrative in the forgotten city of Kayamgadh, has generated significant spin-offs into its universe. With attention to one such spin-off, I will focus critical attention on the issue of the postcolonial gaming of the Museum in A Museum of Dubious Splendors. I will examine the New Museological implications of A Museum of Dubious Splendors, keeping in mind Museologist Eilean Hooper-Greenhill’s assertion of museums embodying “the power to name, to represent common sense, to create official versions, to represent the social world, to represent the past” (Hooper-Greenhill 2001: 2). Oleomingus’ own description of A Museum, as an adaptation of edited, mangled, contested short stories by a fictional Urdu writer, Mir Umar Hassan, eschews the linear narrative production of the colonial museum for a game of meanings, where the player enters rooms according to his choice and constructs his/her own “quiet game about prosaic objects and spurious histories.” ("A Museum" 2018) The paper would take this into account and examine the reconceptualization of the museum space with respect to James Clifford’s sense of museums being “contact zones”: A Museum’s lack of any curator, with its curious blend of colonial and native tales and banal objects defamiliarised by “spurious histories” lends itself to questions of playing the Empire back according to a different episteme, through subaltern histories that the colonial museum space silenced. Paying close attention to the question of postcolonial spatiality in this game, I will analyze the historiographical implications of these identity-scatterings and recuperations at constant play in the structure of the game. Keywords: Museum Studies, Thing Theory, Game studies, Marginal identity, Postcolonial Studies
Keywords: 1-Jeux vidéo; 2-Humanités numériques; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

GSI Adda Talk #2 Riko Banerjee What is it like to be a Gamer or pursue Game Studies in India? - Game Studies India Adda (Game Studies India Adda, 2020)
Video gaming is one of the most popular hobbies in the world, with the gaming industry grossing more revenue than the movie and the music industry combined. The estimated number of gamers across the whole world as of August 2020 is 2.7 billion, which is more than one-third of the world population. The benefits of gaming, as cited by numerous researchers, include a boost in confidence, improved cognitive abilities, stress relief, improved problem-solving skills, enhanced social skills among dyslexic kids, and among many others. Even though video gaming as a hobby and career is slowly getting recognition in India, majority of the population still scoff at the activity, shunning gamers and game researchers alike, citing out-of-context and sometimes even false media propaganda. The challenges faced by a typical gamer in India include lack of information, budget limitation, lack of support from parents and teachers when it comes to teenage gamers, and the overall lack of gaming as a mainstream culture among countrymen. As for someone who wants to pursue Game Studies, there is currently little to no provision for that due to the tightly knit education system in the country and the utter lack of educational institutes offering courses on game studies. We go on to further discuss all of the above challenges and experiences faced by a gamer or someone who wants to pursue game studies in India, in our detailed talk that is scheduled on November 21, 2020.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude de la réception; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

First Person Encounters #5: Abhi, creator of Venba - Game Studies India Adda
Venba is a narrative cooking game, where you play as an Indian mom, who immigrates to Canada with her family in the 1980s. Players will cook various dishes and restore lost recipes, hold branching conversations and explore in this story about family, love, loss and more. More on Steam: https://store.steampowered.com/app/14.... Developer, Abhi, gives Game Studies India an exclusive preview talking about identity, nostalgia, memory and of course, food. In conversation with Poonam Chowdhury and Souvik Mukherjee.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice PANDC; 5-Identités diasporiques; _Nettoyé

First-Person Encounters #4: Poornima Seetharaman - Game Studies India Adda (Game Studies India Adda, 2021)
First Person Encounters is a series of podcasts presented by Games Studies India, about our first experiences with Games while growing up in India. This our third podcast where we talk with Poornima Seetharaman. She is the first Indian to be inducted in the Women in Games (WIGJ) Hall of Fame and is also the lead game designer at Zynga. Hear as we talk about her foray in the world of gaming.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Humanités numériques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice PANDC; 5-Créatrice; _Nettoyé

First-Person Encounters #3: Prof. Xenia Zeiler - Game Studies India Adda (Game Studies India Adda, 2021)
First Person Encounters is a series of podcasts presented by Games Studies India, about our first experiences with Games while growing up in India. This our third podcast where we interview Xenia Zeiler, an associate professor of South Asian studies at the University of Helsinki, Finland. Her research is situated at the intersection of digital media, religion, and culture, with a focus on India and the worldwide Indian community.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

First-Person Encounters #2: Satyajit Chakaborty - Game Studies India Adda (Game Studies India Adda, 2021)
First Person Encounters is a series of podcasts presented by Games Studies India, about our first experiences with Games while growing up in India. This our second podcast where we interview Satyajit Chakraborty, a game developer, game designer and researcher. He also founded Flying Robots Studios in 2012 and has made various unique games. Here he talks about his first experiences with gaming in India.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice PANDC; _Nettoyé

Japanese Video Games and Comics in Singapore: Issues in Popularization, Localization and their Implications - Ng Wai-ming, Benjamin (N.D., 1999)
OCLC: 882102421
Keywords: 1-Jeux vidéo; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Games Studies India Adda Talk #11: Marcus Toftedahl - Game Studies India Adda (Game Studies India Adda, 2021)
Remember localization! Game localization from an indie development perspective Abstract: The game industry is today a global industry, where digital storefronts are used to distribute the digital product you are developing. This presents a number of challenges for a small scale game developer and localization is one. The talk will focus on game localization from an indie game development perspective. The research is based on data from field studies in Sweden, China and India and is a part of a PhD project conducted at the Division of Game Development at the University of Skövde, Sweden. Bio: Marcus Toftedahl is a game researcher, developer and lecturer at the University of Skövde, Sweden. His main competences lies within game production, game localization and game design, from a practical and research perspective. Marcus has worked at the University of Skövde since 2009 and has since then co-developed the world's first full concentration game writing education at university level and is teaching game design and game production.
Keywords: 1-Jeux vidéo; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); _Nettoyé

Politics of Production: Videogames 10 years after Games of Empire - Hammar, Emil L.; de Wildt, Lars; Mukherjee, Souvik; Pelletier, Caroline (Games and Culture, 2021)
2019 marked ten years since the publication of Nick Dyer-Witheford and Greig de Peuter’s Games of Empire, which has become a seminal book in videogame cultural criticism. Ten years later, there is still a pressing need for cultural and materialist criticism of the politics of production within game studies. In putting together this special issue, our hope is to identify new developments in the game industry and academia that are emblematic of 21st-century capitalism. Just as Games of Empire popularised critical political-economic perspectives ten years ago, we encourage others, as the authors in this issue did, to continue and maintain investigations into questions of ownership, privatized property, coercive class relations, military operations and radical struggle. Such analyses are necessary not only to trace but also to open up new directions in game culture and academia for decades to come.
Keywords: 1-Jeux vidéo; 2-Étude des industries culturelles; 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

Independent Videogames: Cultures, Networks, Techniques And Politics - Ruffino, Paolo (Routledge, 2021)
Independent Videogames investigates the social and cultural implications of contemporary forms of independent video game development. Through a series of case studies and theoretical investigations, it evaluates the significance of such a multi-faceted phenomenon within video game and digital cultures. A diverse team of scholars highlight the specificities of independence within the industry and the culture of digital gaming through case studies and theoretical questions. The chapters focus on labor, gender, distribution models and technologies of production to map the current state of research on independent game development. The authors also identify how the boundaries of independence are becoming opaque in the contemporary game industry – often at the cost of the claims of autonomy, freedom and emancipation that underlie the indie scene. The book ultimately imagines new and better narratives for a less exploitative and more inclusive videogame industry. Systematically mapping the current directions of a phenomenon that is becoming increasingly difficult to define and limit, this book will be a crucial resource for scholars and students of game studies, media history, media industries and independent gaming.
Keywords: 1-Jeux vidéo; 2-Analyses formalistes; 2-Approches sociologiques; 2-Genre et sexualité; 2-Humanités numériques; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Europe (corpus analysé); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice LGBTQ+; 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice LGBTQ+; 5-Créateur.rice PANDC; _Nettoyé

The Lure of Pokémon: Video Games and the Savage Mind - Nakazawa, Shin'ichi (Japan Publishing Industry Foundation for Culture, 2019)
From its humble beginnings as a video game launched in the mid-90s, Pokémon has become a global entertainment franchise, even reaching into the world via "augmented reality" with the mobile game Pokémon GO. In the work, Nakazawa Shinichi argues that the Pokémon worldview is the best contemporary example of Claude Lévi-Strauss's "savage mind" (la pensée sauvage), suggesting that computer games can often be viewed as attempts to reconnect the human unconscious with the true, hidden essence of nature.
Section: 1 v. (129 p.) : illustrations, couv. illustrations en coul. ; 22 cm
Keywords: 1-Jeux vidéo; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Video Games and the Global South - Penix-Tadsen, Phillip (ETC Press, 2019)
Redefines games and game culture from south to north, analyzing the social impact of video games, the growth of game development and the vitality of game cultures across Africa, the Middle East, Central and South America, the Indian subcontinent, Oceania and Asia.
OCLC: 1104212185
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Humanités numériques; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

Queerness in Play - Harper, Todd; Adams, Meghan Blythe; Taylor, Nicholas (Palgrave Macmillan, 2018)
"Queerness in Play examines the many ways queerness of all kinds - from queer as 'LGBT' to other, less well-covered aspects of the queer spectrum - intersects with games and the social contexts of play. The current unprecedented visibility of queer creators and content comes at a high tide of resistance to the inclusion of those outside a long-imagined cisgender, heterosexual, white male norm. By critically engaging the ways games - as a culture, an industry, and a medium - help reproduce limiting binary formations of gender and sexuality, Queerness in Play contributes to the growing body of scholarship promoting more inclusive understandings of identity, sexuality, and games."–Provided by publisher.
OCLC: 1057550232
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

Who Made Your Phone? Compassion and the Voice of the Oppressed in Phone Story and Burn the Boards - Navarro-Remesal, Víctor; Zapata, Beatriz Pérez (Open Library of Humanities, 2018)
Burn the Boards (Causa Creations, 2015) portrays the life of an Indian worker who recycles electronic waste in a precarious environment. Phone Story (Molleindustria, 2011) simulates the journey and process of production and consumption of mobile phones, from Congo and China to Pakistan. Whereas Phone Story is described as ‘an educational game’ that addresses the player directly as a consumer, Burn the Boards is a resource management puzzle that creates compassion through role playing. These games bring to the fore a hidden reality of the everyday that is ingrained in historical relationships and power dynamics, drawing attention to what Michael Rothberg has recognized as ‘exploitation in an age of globalized neo-liberal capitalism’ (2014: iv). This article explores how these games denounce the smartphone industry by using that same technology. For this purpose, we refer to Game Studies theory on procedural rhetoric; values and ethics; and the role of the player, combined with questions of (neo)colonization, globalization, and neoliberalism drawn from Postcolonial Studies. Our analysis shows the complicity of users and their confrontation with the extreme vulnerability of others, emphasizing how the coloniality of power works in our global consumer society. Thus we study the power relationships described and established by these games, the affective reactions which they seek to trigger, and their potential to transform players from passive observers into ethical players and consumers.
Number: 1
Keywords: 1-Jeux vidéo; 2-Humanités numériques; 2-Pédagogie décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); 5-Autrice; _Nettoyé

Queer Game Studies - Ruberg, Bonnie; Shaw, Adrienne (University of Minnesota Press, 2017)
The in-depth, diverse, and accessible essays in Queer Game Studies use queerness to challenge the ideas that have dominated gaming discussions. This volume reveals the capacious albeit underappreciated communities that are making, playing, and studying queer games, demonstrating the centrality of LGBTQ issues to the gamer world and establishing an alternative lens for examining this increasingly important culture.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Humanités numériques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice LGBTQ+; 5-Autrice; 5-Créateur.rice LGBTQ+; 5-Créatrice; _Nettoyé

Gaming at the Edge: Sexuality and Gender at the Margins of Gamer Culture - Shaw, Adrienne (University of Minnesota Press, 2015)
Video games have long been seen as the exclusive territory of young, heterosexual white males. In a media landscape dominated by such gamers, players who do not fit this mold, including women, people of color, and LGBT people, are often brutalized in forums and in public channels in online play. Discussion of representation of such groups in games has frequently been limited and cursory. In contrast, Gaming at the Edge builds on feminist, queer, and postcolonial theories of identity and draws on qualitative audience research methods to make sense of how representation comes to matter. In Gaming at the Edge, Adrienne Shaw argues that video game players experience race, gender, and sexuality concurrently. She asks: How do players identify with characters? How do they separate identification and interactivity? What is the role of fantasy in representation? What is the importance of understanding market logic? In addressing these questions Shaw reveals how representation comes to matter to participants and offers a perceptive consideration of the high stakes in politics of representation debates. Putting forth a framework for talking about representation, difference, and diversity in an era in which user-generated content, individualized media consumption, and the blurring of producer/consumer roles has lessened the utility of traditional models of media representation analysis, Shaw finds new insight on the edge of media consumption with the invisible, marginalized gamers who are surprising in both their numbers and their influence in mainstream gamer culture.
Keywords: 1-Jeux vidéo; 2-Analyses formalistes; 2-Approches sociologiques; 2-Genre et sexualité; 2-Méthodologie de recherche décoloniale; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; _Nettoyé

Video Games Around the World - Wolf, Mark J. P. (MIT Press, 2015)
Video games have become a global industry, and their history spans dozens of national industries where foreign imports compete with domestic productions, legitimate industry contends with piracy, and national identity faces the global marketplace. This volume describes video game history and culture across every continent, with essays covering areas as disparate and far-flung as Argentina and Thailand, Hungary and Indonesia, Iran and Ireland.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 3-Océanie (corpus analysé); 4-Afrique (lieu de production du savoir); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice PANDC; _Nettoyé

Gaming Globally: Production, Play, and Place - Huntemann, Nina B.; Aslinger, Ben (Palgrave Macmillan, 2013)
Video games are inherently transnational by virtue of their industrial, textual, and player practices. This collection includes essays from scholars from eight countries analyzing game cultures on macro- and micro-levels and investigates the growing transnational nature of digital play
Section: xi, 279 p. : ill. ; 23 cm.
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice PANDC; 5-Créatrice; _Nettoyé

Playing with the Past: Digital Games and the Simulation of History - Kapell, Matthew Wilhelm; Elliott, Andrew B. R. (Bloomsbury Publishing USA, 2013)
Game Studies is a rapidly growing area of contemporary scholarship, yet volumes in the area have tended to focus on more general issues. With Playing with the Past, game studies is taken to the next level by offering a specific and detailed analysis of one area of digital game play – the representation of history. The collection focuses on the ways in which gamers engage with, play with, recreate, subvert, reverse and direct the historical past, and what effect this has on the ways in which we go about constructing the present or imagining a future. What can World War Two strategy games teach us about the reality of this complex and multifaceted period? Do the possibilities of playing with the past change the way we understand history? If we embody a colonialist's perspective to conquer 'primitive' tribes in Colonization, does this privilege a distinct way of viewing history as benevolent intervention over imperialist expansion? The fusion of these two fields allows the editors to pose new questions about the ways in which gamers interact with their game worlds. Drawing these threads together, the collection concludes by asking whether digital games - which represent history or historical change - alter the way we, today, understand history itself.
Google-Books-ID: jXjHAgAAQBAJ
Keywords: 1-Jeux vidéo; 2-Analyses formalistes; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

A Critical Interpretation of a New “Creative Industry” in Turkey: Game Studios and the Production of a Value Chain - Binark, Mutlu; Bayraktutan, Günseli (Computer Games and New Media Cultures: a Handbook of Digital Games Studies, 2012)
In this chapter, the creation of a value chain during the process of digital games development in Turkey is discussed using a critical political economy approach. This study claims to be the first of its kind that intends to examine the topography of the digital game industry in Turkey and gives a brief history and describes the present status of digital games production in Turkey. All the components of a value chain, namely, the industrial structure and development process, publishing and licensing, distribution and marketing structure, labor force, legal regulations, and governmental policies will be considered in that order to map out the present topography of the industry. The final part of the study will deal with possible solutions for further development in the industry. At this point, the study stresses the fact that all components of the value chain must be performed uninterrupted if the actors in Turkey’s digital game industry desire to position themselves as “producers” in global or local markets.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice PANDC; _Nettoyé

Media Heterotopia and Transnational Filmmaking: Mapping Real and Virtual Worlds - Chung, Hye Jean (Cinema Journal, 2012)
Focusing on The Fall (Tarsem Singh, 2006), The World {}Zhangke S\a, 2004), and Avalon (Mamoru Oshii, 2001), this essay proposes a mode of heterotopic perception and analysis that recognizes the composited layers and material residues of giobally dispersed production sites and laboring bodies in mediated transnationa! spaces.
Keywords: 1-Cinéma; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 5-Auteur.rice PANDC; _Nettoyé; _À analyser; _À nettoyer; _À vérifier-Cinéma

Race-based fantasy realm: Essentialism in the world of warcraft - Monson, Melissa J. (Games and Culture, 2012)
This article explores issues of racial essentialism and ethnicity in the massively multiplayer online role-playing game World of Warcraft (WoW). The fantasy world of Azeroth mirrors elements of real-world race-based societies where culture is thought to be immutably linked to race. The notion of biological essentialism is reinforced throughout the gamescape. Race plays a primary role in the social and political organization of Azeroth. Among other things, race determines alliances, language, intellect, temperament, occupation, strength, and technological aptitude. The cultural representation of the respective racial groups in WoW draws upon stereotypical imagery from real-world ethnic groups (e.g., American Indian, Irish/Scottish, Asian, African, etc.).
Number: 1
Keywords: 1-Jeux vidéo; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; _Nettoyé

Beautiful Fighting Girl - Saitō, Tamaki; Azuma, Hiroki (University of Minnesota Press, 2011)
From Nausicaa to Sailor Moon, understanding girl heroines of manga and anime within otaku culture.
OCLC: 897044808
Keywords: 1-Cinéma; 1-Jeux vidéo; 1-TV; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé; _À analyser; _À nettoyer; _À vérifier-Cinéma

Creative Industries Across Cultural Borders: The Case of Video Games in Asia - Tschang, Ted (Creative Economies, Creative Cities: Asian-European Perspectives, 2009)
This chapter examines the relationship between culture, economics and policy within the creative industries (which for the purposes of this paper, are assumed to be equivalent to the cultural industries), and their manifestation in Asia. Addressing any one of these three issues is a challenge in itself, but addressing all three of them together raises the complexity even further. Early writers on the “creative economy” have noted how it works differently from the traditional economy (Florida 2002; Howkins 2001).1 Culture is vitally important to understanding how creative industries develop, but the role of culture in shaping national competitive advantage is not that clear. The same can be said for policy, and a discussion of the triad can be quite convoluted. Having said that, all three levels are still very relevant to the proper description of a creative industry — as I will show in this chapter.This paper attempts to address this triad of issues primarily with a production-and-innovation-oriented view of industrial organisation, bringing in creativity, culture and policy where possible. I shall do this primarily through the lens of one sector in particular — the video games industry — in which Asia has been investing heavily lately, and in which Japan has been an early leader. I will also provide a limited focus on the animation sector for comparative purposes. I will first provide a summary of how creative production in video games occurs in the US, followed by an examination of how Asian patterns compare. In particular, I am interested in whether individual and industrial level creativity differs in Asia. Within Asia, more detailed cases of the Chinese online games industry and the Philippine animation industry will be discussed, but relevant observations are also drawn from general knowledge and a literature review of Japan, Korea and Singapore, as well as interviews which corroborate those observations.
Keywords: 1-Jeux vidéo; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Video Games in Asia - Ng Wai-ming, Benjamin (The Video Game Explosion: a History from Pong to Playstation and Beyond, 2008)
Section: xxi, 380 pages : illustrations ; 26 cm
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

The Video Game Developpement Process - Tschang, Feichin Ted (The Video Game Explosion: a History from Pong to Playstation and Beyond, 2008)
Section: xxi, 380 pages : illustrations ; 26 cm
Keywords: 1-Jeux vidéo; 2-Étude des industries culturelles; 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

The Video Game Explosion: a History from Pong to Playstation and Beyond - Wolf, Mark J. P. (Greenwood Press, 2008)
Video games have become a limitless and multifaceted medium through which major corporations and Hollywood visionaries alike are reaching broader global audiences and influencing cultural trends at a rate unmatched by any other media. This book traces the growth of a global phenomenon that has become an integral part of popular culture.
Section: xxi, 380 pages : illustrations ; 26 cm
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 5-Auteur.rice PANDC; _Nettoyé

The U.S. Video Game Industry: Analyzing Representation of Gender and Race - Dunlop, Janet C. (International Journal of Technology and Human Interaction, 2007)
Today’s media are vast in both form and influence; however, few cultural studies scholars ad-dress the video gaming industry’s role in domestic maintenance and global imposition of U.S. hegemonic ideologies. In this study, video games are analyzed by cover art, content, and origin of production. Whether it is earning more “powers” in games such as Star Wars, or earning points to purchase more powerful artillery in Grand Theft Auto, capitalist ideology is reinforced in a subtle, entertaining fashion. This study shows that oppressive hegemonic representations of gender and race are not only present, but permeate the majority of top-selling video games. Finally, the study traces the origins of best-selling games, to reveal a virtual U.S. monopoly in the content of this formative medium.
Number: 2
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; _Nettoyé

The potential of America's Army, the Video Game as Civilian-Military Public Sphere - Li, Zhan (Massachusetts Institute of Technology, 2003)
The US Army developed multiplayer online First Person Shooter video game, America's Army, was examined as the first instance of an entirely state-produced and directed enterprise leveraging video game popular culture. Specifically, this study is concerned with the potential of the America's Army gamespace as a US civilian-military public sphere of the Information Age, as assessed through Habermasian theories of democratic communication. Interview fieldwork was carried out in several America's Army game communities including those of real-life military personnel, Christian Evangelicals, and hackers. The political activities of these exceptional game communities are considered for the ways they escape and transcend current critical theories of Internet-based public spheres.
Accepted: 2007-10-22T19:02:27Z
Keywords: 1-Jeux vidéo; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Japanese Video Games in Singapore: History, Culture and Industry - Ng Wai-ming, Benjamin (Asian Journal of Social Science, 2001)
Globalization of Japanese popular culture is reshaping the global cultural landscape. Some forms of Japanese popular culture (such as video games animation and sushi) are well-received internationally, whereas others (such as pop music, films and TV dramas) are only popular in Asia. Of all forms of Japanese popular culture, video game is perhaps the most powerful due to its strong universal appeal. It has dominated the world market since the mid-1980s. This article uses Singapore as a case study to demonstrate the global popularization of Japanese video games. There has been a boom of Japanese popular culture in Singapore in the 1990s. In particular, Japanese video games, comics and animation have become an integral part of youth culture in Singapore (Ng, March 2000: 234-246; Ng, May 2000: 44-56; Ng, June 2000: 1-14). Video game is a neglected topic in cultural studies. Although there are some basic studies of Japanese video games in the Western world (Hayes & Disney, 1995; Herz, 1997; Kinder 1991; Monopolies, 1995; Sheff, 1993), its impact in Asia is largely unknown. This article is a preliminary study of the Japanese video game culture and industry in Singapore from historical and socio-cultural perspectives, focusing on consoles, games and players. Based on interviews, questionnaires and data from newspapers and magazines, this research aims at pro viding a general overview of the history and impact of Japanese video games in Singapore. All the data and analyses are basic and this is beyond the scope of this paper to discuss any particular issue or theory in details. This paper consists of four sections. The first three sections outline the development of home video game consoles, handheld electronic games and game arcades respectively. The concluding section pinpoints the characteristics of the video
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé